“I agree with you”- a corpus based study of agreement - Andy Seto (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2009)
The paper is a corpus-based study comparing the expressions of agreement in textbook English and in genuine English to suggest how corpus data can help to improve the authenticity of English textbook material in Hong Kong. The data sets included textbook data and selected parts of the Hong Kong Corpus of Spoken English. Both quantitative and qualitative approaches are used to analyze the data. The findings show that there are significant differences between textbook English and genuine English in expressing agreement. Not only the expressions of agreement but also the ways in which agreement is expressed vary. Many expressions of agreement mentioned in the textbooks cannot be found in the corpus data sets. Simultaneously,the common ways of expressing agreement in naturally occurring spoken English are not introduced in the textbook data. It is argued that textbook writers need to enhance the authenticity of textbook material for language learners by using examples from genuine English and corpus data is one importance source in providing naturally occurring expressions of agreement for local secondary schools students in Hong Kong